Internet Marketing as a Modern Enterprise Communication Tool - Fomichenko, I.; Barkova, S.; Dykan, A.; Kosik, K.; Kozlova, K. (Економічний вісник Донбасу, 2020)
The article identifies the need for the use of Internet marketing technologies to promote goods and services in a modern domestic enterprise. Based on the analysis, the need to improve the marketing, sales and communication policy of domestic enterprises using the Internet is substantiated. The main marketing processes that are implemented using Internet marketing technologies, which include marketing research on the Internet, marketing communications on the Internet and promotion and marketing of products over the Internet. The main types of Internet marketing at a modern enterprise are studied. Current trends in Internet marketing communications are identified. The advantages of the use of Internet technologies in the marketing activities of enterprises are substantiated, which also affect the efficiency (or empowerment) not only in marketing activities, but also in other areas of the enterprise. У статті визначено необхідність застосування
маркетингових Інтернет-технологій просування товарів і послуг на сучасному вітчизняному підприємстві. На основі проведеного аналізу обґрунтовано необхідність удосконалення маркетингової збутової та комунікаційної політики вітчизняних підприємств із використанням Інтернету. Визначено основні маркетингові процеси, які реалізуються за допомогою технологій Інтернет-маркетингу, до яких належать маркетингові дослідження в Інтернеті, маркетингові комунікації в Інтернеті та просування і збут продукції через Інтернет. Досліджено основні види Інтернет-маркетингу на сучасному підприємстві. Визначено актуальні тенденції маркетингових Інтернет-комунікацій. Обґрунтовано переваги застосування Інтернет-технологій у маркетинговій діяльності підприємств, які впливають також на ефективність (або розширення можливостей) не тільки у маркетинговій діяльності, але й в інших сферах діяльності підприємства. В статье определена необходимость использования маркетинговых Интернет-технологий продвижения товаров и услуг на современном отечественном предприятии. На основе проведенного анализа обоснована необходимость усовершенствования маркетинговой сбытовой и коммуникационной политики отечественных предприятий с использованием Интернета. Определены основные маркетинговые процессы, которые реализуются с помощью технологий Интернет-маркетинга, к которым относятся маркетинговые исследования в Интернете, маркетинговые коммуникации в Интернете и продвижение и сбыт продукции через Интернет. Исследованы основные виды Интернет-маркетинга на современном предприятии. Определены актуальные тенденции маркетинговых Интернет-коммуникаций. Обоснованы преимущества применения Интернет-технологий в маркетинговой деятельности предприятий, которые влияют также на эффективность (или расширение возможностей) не только в маркетинговой деятельности, но и в других сферах деятельности предприятия.